Post-stroke shoulder pain and quality of life among stroke patients in Hospital University Sains Malaysia (HUSM) - Zainudin, Zafirah Najwa (Universiti Sains Malaysia, 2013)
Post-stroke shoulder pain (PSSP) is a common complication after stroke. Substantial evidence can be found in the literature to show the occurence as well as a facts on PSSP including definition, onset, causes and effects, major symptoms and signs, impacts on QOL, and instrumentation. The general objective of the study was to determine PSSP among stroke patients in Hospital University Sains Malaysia (HUSM). This cross sectional study was done on 83 stroke patients as respondents by convenience sampling method and validated questionnaires such as socio-demographic data. Visual Analogue Scale to determine the level of pain, and elements of Stroke-Specific Quality of Life were given to the respondents and only 57 respondents that fits the inclusion criteria that were recruited for this study. The response rate for this study was 68.67%. Data was statistically analyzed using software package SPSS version 22.0. The data was analyzed using descriptive statistic and Chi-square test. The result showed that the occurence of PSSP among respondents was significantly high (68.67%). As for level of PSSP, most of the respondents (n= 29, 50.9%) were had moderate pain regarding PSSP. Besides that, most of respondents (n=21, 36.8%) had high QOL, followed by respondents (n=!9. 33.3%) had moderate QOL, and then respondents (n=!7, 29.8%) had low QOL. Accordingly, there was association found between level of PSSP with QOL in respondents with PSSP (/?<0.05). Therefore, further study need to be done to emphasized on the prevalence, preventive measures, support from health professionals, screening programmes and to provide important information as well as to improved public understanding about PSSP.